Prior pandemics. looking to the past for insight into the COVID-19 pandemic - Philip A. Mackowiak (Greater Baltimore Medical Center, 2021)
COVID-19 is not the world's first pandemic, not its worst, or likely to be its last. In fact, there have been many pandemics throughout history with lessons for the current one. The most destructive pandemic of all time, at least in terms of the number of people killed in the shortest time, was the "Spanish flu" pandemic of 1918/1919. Why did it happen? What lessons did it teach us? And could it happen again? These questions are addressed in the context of the current COVID-19 pandemic and several other nearly equally devastating pandemics of earlier times